Efecto de la adición de microorganismos benéficos (Rhodopseudomonas spp, Lactobacillus spp, Sacharomyces spp), en la producción de huevos de codorniz (Coturnix coturnix japónica) - Mendieta Suárez, Edison Francisco (2015)
The productive performance of quails (Coturnix coturnix japonica) in the stage of egg production under the effective microorganisms influence on T1 dose of 0.5ml / Lt evaluated. water, T2 1ml / Lt water, T3 2ml / Lt. water, more efficient control without bodies; was held in the county and province of Loja, with an average height of 2,200 meters, was applied an experimental design randomized blocks with 4 treatments and 3 repetitions with a total 96 quails 40 days old, eight quail was used for experimental unit for a period of 14 weeks, the variables evaluated were: feed intake, weight, feed conversion, egg production, mortality and cost-benefit results .The variable egg production; the most effective treatment is with a percentage T3 with 76.28%; followed by treatment 2 with 76.40%, in order of efficacy, with respect to profitability expressed in cost / benefit ratio, the best treatment T3 with a ratio of 1.32; with a rate of return of 32.99%, followed by the T1 with a ratio of 1.30 and a yield of 30.86%, followed by the T2 with a ratio of 1.22 and a return on 22.94, and as the last witness at a ratio of 1.20 with a yield of 20.61%.